A study on effectiveness of anti-smoking advertising toward society / Aiman Iqwan Kholid - Kholid, Aiman Iqwan (2019)
This research focuses much impact can be produce from anti-smoking advertising toward the society in urban area. Thus due to urban have multiracial society as well as different types of demographics. Smoking has been one of the symptoms of an unhealthy lifestyle in Malaysia. Through the year, there have been various types of anti-smoking campaigns being made from the government in dealing with smokers and prevent the community from falling into an unhealthy lifestyle. The main objective of this study is to investigate the impact from the anti-smoking advertising toward smoker itself or the society. The purpose of this study is to create an awareness of smoking effect among society regarding the campaign or the advertisement that been create, to investigate the concept, storyline which appeal in anti-smoking advertisement and to create the better method in order to make a better advertisement. All the data that been collected via quantitative. A questionnaire was selected as main method to know the effectiveness from the advertisement. Beside from the survey, the results have been collected through observation and from previous research. This researcher picked Bangsar as research area due to this area have a plural population and easy for researcher to make research there.